Development prototype of graceful interaction in photo gallery / Muhamad Faisal Othman - Othman, Muhamad Faisal (2012)
This project is about developing a prototype of photo gallery using Graceful Interaction design which consists of 4 elements of movement which in Laban Effect of Movements. The movements are been displayed in each and every photo gallery that has been develop. The objective of this photo gallery is to identify the user acceptance, perception and experience while using the photo gallery whether they are satisfied, happy, and impressed while browsing the photo gallery that consist of all the elements. There are five samples that have been developed which have its own elements and there is one sample that has the combination of all the elements and become one photo gallery which consists of all the movements from other samples. All five samples is been tested by ten users and from the tests, the information has been collected in order to identify the result of the user experience such as simple reaction and comment will be take note in order to identify whether all this element has an effect to the user if it is apply in the photo gallery in any of the websites. This project also is to create an understanding and experience to the user about Graceful Interaction design which use Laban Effect of Movement in photo gallery and from the user experience this project able to identify the user acceptance, satisfaction and the effect towards their experience whether they like or dislike on each and every sample that has been showed in this project. In this report also explains about the tools and method in developing the photo gallery.